Photon Collisions with Atoms and Molecules - Singor, Adam Julianus Chant (Curtin University, 2025)
This thesis focuses on the theoretical and computational study of photoionisation, Rayleigh, and Raman scattering on the alkali atoms, which can be well-approximated as quasi one-electron systems, and the hydrogen molecule H2, its ion, and its isotopologues. Photon scattering methods previously developed for the hydrogen atom are extended to quasi one-electron atoms, a fully relativistic formulation, and then to the diatomic hydrogen molecule.